STRATEGI PEMBELAJARAN FIQIH SHALAT PADA ANAK USIA SEKOLAH DASAR DI TAMAN PENDIDIKAN AL-QUR’AN - Tauhid, Moh. Tauhid (STAI Sangatta Kutai Timur, 2024)
The obligation to learn the fiqh of prayer is not only carried out by a male who has reached puberty but should be learned from an early age at the age of children. The fact that is often found, is that in carrying out prayers, children of elementary school age and even middle school age still do not understand the fiqh of prayer. The purpose of this study was to find out the concepts and types of learning strategies, learning strategies for practicing fiqh for elementary school-aged children and knowing the problems of learning prayer fiqh for elementary school-aged children at TPA Darus Sakinah Sangatta Utara. The method used in this research is the descriptive qualitative method, and data analysis uses Miles & Huberman data analysis. The results showed that there were many kinds of learning strategies, namely: lecture strategies, discussions, demonstrations, simulations, field experiences, mind mapping, and drama. There are also expository learning strategies, inquiry, problem-based, cooperative, affective, contextual, and thinking skills. The learning strategy for fiqh prayer at TPA Darus Sakinah uses tikrār strategies, demonstrations, and field experiences. The problems are the learning facilities and infrastructure that are less supportive, the age and class level of the students are different, the arrival of the students is not the same, the students are over capacity, and the lack of teachers